THE GROUPING OF VILLAGES ON KB SUPPORTING INDICATORS AS A BASIC MAPPING FOR FORMATION KAMPUNG KB IN SURABAYA - Erma Oktania Permatasari; Wahyu Wibowo; Budi Priyono (JOURNAL ASRO, 2021)
Population problems in Indonesia is still important and complex issues that must be resolved. Indonesia has the fourth largest population after China, India and the United States. Uncontrolled population growth will cause problems, such as lack of employment opportunity, unemployment and increased crime. To solve these problems, the government through BKKBN (The National Population and Family Planning) increase the promotion of Family Planning (KB) with the slogan "two children are enough". To support the success of KB program, the government is introducing Kampung KB program. Based on description, this research will be investigated how the grouping of villages based on KB supporting indicators as basic mapping for formation Kampung KB in Surabaya, because Surabaya is the second largest city in Indonesia after Jakarta. The variables used in this research are contraceptive prevalence rate/ CPR, the survival rate of contraceptive use, mix contraceptive, unmet need, the number of pra prosperous and prosperous I familyies, the number of toddler, the number of elderly, long-term contraceptionon method, the number of male participation KB, the number of women of childbearing age, the number of patriarch by employment status, the number of patriarch by education level, the number of population, and the number of teenagers marriages under 20 years old. The results show that using cluster hierarchy analysis and cluster non hierarchy analysis, the optimum grouping is 4 groups. Keywords: Population, KB program, Kampung KB.